QUALITY OF ARCHITECUTRE AND PUBLIC SPACES AS A RESULT OF COUNTRY’S PUBLIC PROCUREMENT CULTURE - Kowalczyk, Maciej Wojciech (Journal of Education Culture and Society, 2019)
Thesis. The quality of emerging public spaces and buildings is related to the public procurement culture of a given country. One can not count on achieving high quality public space, architecture without a democratic debate on the subject. The space, which is decided only by a small group of technocrats, the project, which is subject to only the price criterion, results in accidental solutions.Methods. The article shows the basic methods provided for by law to select public projects. Indicates the advantages and disadvantages of individual processes. It analyzes examples of appreciated realizations that arose as a result of architectural competitions.Results. Tools provided in the public procurement law, such as social debate in the form of architectural competitions build a better quality of the created space. The existence of such a link is proven by the awards granted to spaces completed under such processes.Conclusions. Projects created using these tools account for less than 1% of all public procurement in Poland. One should strive for a change that would promote these processes, especially outside large cities, thus increasing the quality of spaces created from public money.